Health Care Quality Indicators Project Conceptual Framework Paper - Kelley, Edward (OECD Publishing, 2006)
This paper represents an attempt to set out a conceptual framework for the OECD's Health Care Quality Indicator (HCQI) Project. Two main issues are tackled: what concepts, or dimensions, of quality of health care should be measured and how, in principle, should they be measured. The need for a conceptual framework for the Project was expressed by a large group of participating countries. In interviews by the OECD Secretariat with member countries in April and May 2005, country experts and delegates to the Group on Health reiterated the need for a framework for the OECD's health care quality work. Countries stated that the framework should be: a) based on country experience and b) could be used to guide both current and future work by the OECD in health care quality measurement and monitoring
Keywords: Social Issues/Migration/Health